2022
DOI: 10.1002/jsfa.12053
|View full text |Cite
|
Sign up to set email alerts
|

Towards an alcohol‐free process for the production of palm phytonutrients via enzymatic hydrolysis of crude palm oil using liquid lipases

Abstract: BACKGROUND Crude palm oil (CPO) is rich with phytonutrients such as carotenoids and tocols which possesses many health benefits. The aim of this research was to develop a methanol‐free process to produce palm phytonutrients via enzymatic hydrolysis. In this work, triacylglycerol was hydrolyzed into free fatty acids (FFAs) using three different types of liquid lipases derived from Aspergillus oryzae (ET 2.0), Aspergillus niger (Habio) and Candida antartica (CALB). RESULTS ET 2.0 was found to be the best enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ling et al [37] reported that BHA and α-tocopherol at 200 ppm have similar inhibitory effects in preventing the triglyceride hydrolysis of sunflower oil over 24 days of accelerated storage (65 • C). Adiiba et al [38] revealed that phenolic antioxidants (TBHQ, BHT, and BHA) did not interfere with or enhance FFA production and preserved carotene and tocopherols during the enzymatic hydrolysis of crude palm oil as follows: TBHQ > BHT > BHA. In a study conducted on the stability of chia oil (Salvia hispanica L.), Bodoira et al [39] showed no significant increase in acidity over time (p ≤ 0.05) for oil containing TBHQ as synthetic antioxidant compared to natural antioxidants (tocopherol, ascorbyl palmitate, and rosemary extract) in fluorescent lighting (800 Lux) or in the dark for 300 days.…”
Section: Effect Of Thermal Storage On Free Fatty Acids (Ffas)mentioning
confidence: 99%
“…Ling et al [37] reported that BHA and α-tocopherol at 200 ppm have similar inhibitory effects in preventing the triglyceride hydrolysis of sunflower oil over 24 days of accelerated storage (65 • C). Adiiba et al [38] revealed that phenolic antioxidants (TBHQ, BHT, and BHA) did not interfere with or enhance FFA production and preserved carotene and tocopherols during the enzymatic hydrolysis of crude palm oil as follows: TBHQ > BHT > BHA. In a study conducted on the stability of chia oil (Salvia hispanica L.), Bodoira et al [39] showed no significant increase in acidity over time (p ≤ 0.05) for oil containing TBHQ as synthetic antioxidant compared to natural antioxidants (tocopherol, ascorbyl palmitate, and rosemary extract) in fluorescent lighting (800 Lux) or in the dark for 300 days.…”
Section: Effect Of Thermal Storage On Free Fatty Acids (Ffas)mentioning
confidence: 99%
“…Besides the transesterification of TAGs and esterification of free fatty acids (FFAs) to produce esters, there has been increasing interest among researchers in utilizing Eversa lipases for FFA production via oil hydrolysis . An example is the study by Adiiba et al, which reported on the high catalytic performance of Eversa Transform 2.0 (ET2) lipase in the hydrolysis of crude palm oil, in comparison with other lipases, such as lipase derived from Aspergillus niger (Habio) and Candida Antarctica lipase B (CALB) . The Eversa lipase employed in this study, High Strength FG Eversa Transform 2.0 (HS FG ET2), is a novel version of ET2, specifically engineered and enhanced for catalyzing hydrolysis reactions.…”
Section: Introductionmentioning
confidence: 99%